BENZOLNING ISHLATILISHI ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Benzene is a widely used industrial chemical known for its applications in the production of plastics, synthetic fibers, rubber, and other essential products. However, its toxicological profile, including carcinogenic properties, poses significant health risks to humans. This article explores the industrial uses of benzene, its environmental and health impacts, and the regulatory frameworks governing its use. A balanced understanding of benzene's benefits and dangers is crucial for industries, policymakers, and health professionals.